2018
DOI: 10.1177/2045894018776894
|View full text |Cite
|
Sign up to set email alerts
|

The impact of right ventricular pressure and function on survival in patients with pulmonary vein stenosis

Abstract: Pulmonary vein stenosis (PVS) is associated with pulmonary hypertension (PH), but there is little information regarding the impact of PH on right ventricular (RV) systolic function and survival. We conducted a retrospective cohort study of our patients to explore this and other aspects of pulmonary hemodynamics with PVS. RV function was assessed using qualitative two-dimensional echocardiography. The ratio of systolic pulmonary artery (PA) and aortic pressures (PA:Ao) at cardiac catheterization reflected pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Pulmonary vasodilators could reduce RV afterload and postpone the need for surgery, but may induce pulmonary oedema, particularly when vasodilation occurs in both stenotic and unaffected territories. Currently, approximately 30% of paediatric patients with PVS are on pulmonary vasodilator treatment, with sildenafil being the most commonly administered drug [7,24]. Our study showed that, although the pulmonary small arteries from the HP/LF territories respond better to sildenafil in vitro than those from HP/HF territories, sildenafil treatment did not result in overt pulmonary oedema in vivo.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Pulmonary vasodilators could reduce RV afterload and postpone the need for surgery, but may induce pulmonary oedema, particularly when vasodilation occurs in both stenotic and unaffected territories. Currently, approximately 30% of paediatric patients with PVS are on pulmonary vasodilator treatment, with sildenafil being the most commonly administered drug [7,24]. Our study showed that, although the pulmonary small arteries from the HP/LF territories respond better to sildenafil in vitro than those from HP/HF territories, sildenafil treatment did not result in overt pulmonary oedema in vivo.…”
Section: Discussionmentioning
confidence: 59%
“…These studies identified a number of risk factors that result in decreased survival and increased risk of restenosis; among them were the number of stenotic pulmonary veins (three or more affected veins had poorer outcome then two or fewer stenotic pulmonary veins), bilateral disease and small body size for gestational age. Another important determinant of mortality is the severity of PH and concomitant RV dysfunction [24].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who are at risk of a poor outcome include those with a younger age and/or lower weight at presentation, a higher number of affected veins, higher severity of disease in the affected veins, severe secondary PH, presence of RV dysfunction, and aspiration. 13,29,35,[43][44][45][46][47][48] Patients with single-ventricle physiology are particularly vulnerable. Patients who respond to therapy thrive, require fewer and less frequent interventions, have shorter hospital stays following reintervention, and have declining RV pressure.…”
Section: Surgerymentioning
confidence: 99%
“…Without intervention, RV hypertension can lead to restricted cardiac output and death. 47 Although historically controversial, there is growing evidence suggesting not only the safety of pulmonary vasodilators in the setting of PVS but also efficacy and utility in patients with severe PVS. 47,50,65 Any use of standard pulmonary vasodilators in this population should be done so with due caution and carefully planned reevaluation to determine the efficacy or progression of PVS.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Pediatric intraluminal pulmonary vein stenosis (PVS) is caused by the hyperplasia of myofibroblast-like cells in a myxocollagenous matrix which compromises flow and leads to pulmonary hypertension, right heart failure, and death [ 1 , 2 , 3 ]. Factors associated with patient survival include age, overall disease burden, the severity of pulmonary hypertension, and right ventricular function [ 4 , 5 , 6 , 7 , 8 , 9 ]. Aggressive subtypes involve multiple veins and have a high incidence of restenosis, irrespective of intervention [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%